The Use of An Arduino Uno Ultrasonic Sensor in Desalination Equipment's Water Filling Control - Larasati Putri Hapsari; Roberto Patar Pasaribu; Ika Anjani (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
A sensor called an ultrasonic sensor works by converting electrical quantities into physical quantities (sound) and vice versa. An Arduino Uno is required to activate the system's ultrasonic sensor. The reservoir's water level is determined using ultrasonic sensors. The purpose of this investigation is to learn how to put together, program, and utilize the HC-SR04 Arduino Uno ultrasonic sensor with the Arduino IDE (Integrated Development Environment) application. Controlling the water in the desalination system is required so that the water entering the reservoir does not waste or overflow and pollute the desalinated water. An ultrasonic sensor is attached to a seawater desalination system using the evaporation method, and the sensor is put on the edge of the evaporation pond in order to conduct experimental testing of the ultrasonic sensor on the device. The desalination tool can operate more efficiently and under control with the help of the HC-SR04 ultrasonic sensor by automatically filling the water in the evaporation pond. The sensor will automatically supply the water shortage when the seawater evaporates. Results of experimental observations made with the HC-SR04 ultrasonic sensor on an evaporation bath with three water filling cycles are available. so that after 7 days, 13% of the volume that was filled in the evaporation basin has evaporated.